FOCALIZATION FORM IN NOVEL MENCARI PEREMPUAN YANG HILANG BY IMAD ZAKI: NARROTOLOGICAL STUDY - Rendy Pribadi; Ninuk Lustyantie; Zuriyati Zuriyati (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
This research seeks to examine the storytelling elements (storytelling style) in the novel Looking for the Missing Woman by Imad Zaki in the form of dialogue, and the behavior of the characters. There is (finding) a different style when several characters tell their lives, starting from changing characters in storytelling so that they reveal some human traits in this novel. Analysis in narratology tries to reveal this characteristic with three forms of analysis, namely internal and external focalization and external and internal focalization. Internal focalization attempts to describe the dialogue of the "self" from within and external focalization is the feeling that is described by others. The other forms of focalization are outward and inward. Outward focalization is a description of a character based on his outward appearance. It's different with the outward focuser, the inward focuser uses mental and memory elements when analyzing it. This study uses a qualitative approach with data collection methods using the library method. The interpretation of the text is obtained from the monologues and dialogues in each text of this novel. Using content analysis techniques. The author finds a number of techniques (styles) of storytelling; 1. Internal focalization (“I”) based on the narrator, 2. External focalization in the form of symbols, 3. Harmonious and sad story in one frame of the novel.